2012
DOI: 10.1111/ffe.12003
|View full text |Cite
|
Sign up to set email alerts
|

Strain ratcheting and stress relaxation around interference‐fitted single‐holed plates under cyclic loading: experimental and numerical investigations

Abstract: Longitudinal strain ratcheting and stress relaxation in interference‐fitted single‐holed plates were investigated both experimentally and numerically. In the experimental part single‐holed plates made from Al‐alloy 7075‐T6 were force‐fitted with oversized pins to create 1% and 2% nominal interference fit sizes. Then these plates (specimens) were instrumented with dynamic strain gauges in longitudinal direction around the hole to measure the strain during interference fit and strain ratcheting during subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Mean stress relaxation behavior of different aluminum alloys has been studied experimentally and numerically recently by Arcari et al, 12,14 Chakherlou et al, [15][16][17] Hong Hao, 18 and Maximov 19,20 and also significant results were provided due to experimental and numerical studies. It is demonstrated that the rate of mean stress relaxation during the primary cycles is higher for large strain amplitude compared with low strain amplitude; hence, it is clear that the effect of mean stress on fatigue life of mechanical components will disappear faster for higher strain amplitudes.…”
mentioning
confidence: 99%
“…Mean stress relaxation behavior of different aluminum alloys has been studied experimentally and numerically recently by Arcari et al, 12,14 Chakherlou et al, [15][16][17] Hong Hao, 18 and Maximov 19,20 and also significant results were provided due to experimental and numerical studies. It is demonstrated that the rate of mean stress relaxation during the primary cycles is higher for large strain amplitude compared with low strain amplitude; hence, it is clear that the effect of mean stress on fatigue life of mechanical components will disappear faster for higher strain amplitudes.…”
mentioning
confidence: 99%
“…A comprehensive plasticity model should be able to predict the following phenomena: Bauschinger effect, hardening/softening behaviour, mean stress relaxation, strain ratcheting, and load history memory. Considering the importance of strain ratcheting in fatigue life of mechanical joints, special emphases have been given to this issue, and many constitutive equations have been developed for ratcheting response simulations. In this study the Chaboche kinematic hardening models 1986 (3 decomposed rules) and 1991 (fourth rule with a threshold) used for analysing the strain ratcheting behaviour of Al‐alloy 2024‐T3 sheets.…”
Section: Constitutive Modelling: Cyclic Plasticitymentioning
confidence: 99%
“…Chakherlou and Ajri performed experiments and numerical analysis to evaluate the longitudinal ratcheting and stress relaxation in interference‐fitted single‐holed plates. They reported larger magnitudes of ratcheting strains as cyclic load level increased.…”
Section: Introductionmentioning
confidence: 99%